2011
DOI: 10.1007/s10620-011-1943-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Lactobacillus reuteri BR11 Mutant Deficient in the Cystine-Transport System in a Rat Model of Inflammatory Bowel Disease

Abstract: Background: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Lactobacillus reuteri BR11 reduces the severity of experimental IBD, principally via a mechanism of thiol production [43]. Male Sprague–Dawley rats were administered 2% DSS to induce colitis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus reuteri BR11 reduces the severity of experimental IBD, principally via a mechanism of thiol production [43]. Male Sprague–Dawley rats were administered 2% DSS to induce colitis.…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic administration partially alleviated the DSS effects, with a minor improvement in the crypt area. The administration of the mutant strain to colitic animals failed to produce significant differences when compared with the DSS control [43]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies have highlighted the profound effect of diet on gut microbiota composition and the connection to immune pathways [55,56,57]. Inadequate colonization of infant gut or alteration in the microbiota profile (dysbiosis) is now considered a strong risk factor for chronic disorders, such as allergic and autoimmune diseases [58,59,60]. A recent study found a significant relationship between gut microbiota constituents at one month of age and the later development of specific serum IgE against food proteins.…”
Section: Gut Microbiota As a Nutriepigenomic Playermentioning
confidence: 99%
“…Lactobacillus has been reported to be beneficial to the host and its increase may be related to the relief of colitis . However, different strains of Lactobacillus may have different effects . Many uncultured Lactobacillus were detected in 5‐ASA‐treated colitis group in the current study.…”
Section: Discussionmentioning
confidence: 48%